Burden of prostate cancer and relationship with the human development index (HDI) in the in Asia: A study Global Burden disease in 2019 - Elham Goodarzi; Fazlollah Fathollahi; Zaher Khazaei (Babol University of Medical Sciences, 2023)
Background: Prostate cancer (PC) ranks as the second most commonly diagnosed neoplasia and the fifth cause of death in men with cancer, with an increasing trend in incidence. The aim of this study was to investigate the epidemiological situation of prostate cancer and relationship with the human development index (HDI) in the Asian continent. Methods: All accessible data sources from the 2019 Global Burden of Disease study were used to estimate the prevalence, mortality and disability-adjusted life years and burden prostate cancer in Asia from 1990 to 2019. We estimated all-cause and cause-specific mortality, years of life lost (YLLs), years lived with disability (YLDs) and disability-adjusted life-years (DALYs). All estimates were presented as counts and age-standardized rates per 100 000 population, with uncertainty intervals (UIs). Concentration Index analysis and Concentration Curve were used to determine the relationship between Prostate cancer burden and human development index. Results: The highest incidence of prostate cancer in Asia in 2019 is Japan (90.5 per 100,000) and the highest mortality rate is Georgia (27.87 per 100,000). The highest DALY, YLL and YLD of prostate cancer is Georgia. The results showed that the percentage of changes in the incidence in 1990-2019 was positive in all countries of the Asian continent except for Afghanistan and Kyrgyzstan. The results of the concentration index showed that the incidence and mortality of prostate cancer is more concentrated in countries with a high HDI level. Examining the DALY, YLL and YLD index also showed the value of concentration index, which shows that DALY, YLL and YLD of prostate cancer are more concentrated in countries with high HDI level. Conclusion: Given that the incidence, mortality and burden of prostate cancer are increasing in most Asian countries and are mostly concentrated in the HDI drawers, obtaining accurate estimates in these countries to prepare for the potential change in public health burden due to this disease which is very important.